2019
DOI: 10.1055/s-0039-1698285
|View full text |Cite
|
Sign up to set email alerts
|

Management of Malignant Pleural Effusions—What Is New

Abstract: Malignant pleural effusion (MPE) is a common and challenging problem. Patients affected by MPE have a poor prognosis and suffer from breathlessness and impaired quality of life. The management of MPE has barely changed for many decades; however, recent research has driven new paradigms in the diagnosis and treatment of MPE and stimulated novel concepts that are being evaluated in many ongoing studies. This review provides an overview of recent advances in the diagnosis of MPE, including new cytopathology and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 96 publications
0
14
0
2
Order By: Relevance
“…[1][2][3] However, in recent years, a number of randomized clinical trials and high-quality studies have shown IPC to be effective and similar to pleurodesis in terms of symptom control and improvement of the quality of life, and with significant benefits for patients such as ambulatory management and the need for fewer additional pleural procedures. [4][5][6] Recent systematic reviews comparing the effectiveness of IPC versus pleurodesis concluded that the two approaches share a similar success rate for the control of MPE.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] However, in recent years, a number of randomized clinical trials and high-quality studies have shown IPC to be effective and similar to pleurodesis in terms of symptom control and improvement of the quality of life, and with significant benefits for patients such as ambulatory management and the need for fewer additional pleural procedures. [4][5][6] Recent systematic reviews comparing the effectiveness of IPC versus pleurodesis concluded that the two approaches share a similar success rate for the control of MPE.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] The latest recommendations for the treatment of MPE therefore position IPC as a first-line treatment for the management of MPE. [4][5][6] The choice between IPC and pleurodesis should be based on the risk/benefit balance in each case and the cost of each procedure. [4][5][6] Cost-effectiveness analyses are an economic evaluation model that provides a framework for comparison of the cost and clinical outcomes of health care interventions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NCCN Guidelines make it clear that cytological specimens are available for genetic testing. Malignant pleural effusion exists in nearly half of advanced NSCLC patients [2-4], which is a convenient cytological specimen for gene detection, but most cancerous pleural effusion is bloody. Bloody pleural effusion (BPE) were usually centrifuged or made cell blocks for the next nucleic acid extraction and genetic testing.…”
Section: Introductionmentioning
confidence: 99%
“…Malignant pleural effusion (MPE), often originates from most malignant tumors, is a common and challenging problem. Patients often suffer from breathlessness, poor quality of life (QOL) and prognosis [1][2]. Control of the effusion signi cantly reduces morbidity, and improves quality of life.…”
Section: Introductionmentioning
confidence: 99%